2023
DOI: 10.1098/rsta.2023.0130
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmaceutical interventions for COVID-19: a systematic review on environmental control measures

Anagha Madhusudanan,
Christopher Iddon,
Muge Cevik
et al.

Abstract: The purpose of this review was to identify the effectiveness of environmental control (EC) non-pharmaceutical interventions (NPIs) in reducing transmission of SARS-CoV-2 through conducting a systematic review. EC NPIs considered in this review are room ventilation, air filtration/cleaning, room occupancy, surface disinfection, barrier devices, CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For example, cohorting/batching attendees with managerial and environmental controls appeared to help in managing crowding (and see [28]). More generally, environmental and service restructuring, including seating plans, floor markings, food and beverage delivery (and remote ordering), and physical barriers/pathways, worked well to shape the behaviors of large numbers of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cohorting/batching attendees with managerial and environmental controls appeared to help in managing crowding (and see [28]). More generally, environmental and service restructuring, including seating plans, floor markings, food and beverage delivery (and remote ordering), and physical barriers/pathways, worked well to shape the behaviors of large numbers of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal Society recently conducted a series of reviews looking at the efficacy of nonpharmaceutical interventions during COVID-19, which suggested that social distancing measures can be highly effective in mitigating the risk of contagion within a population [18]. Environmental controls may also be advantageous, though more focused research is required in that regard [28]. A separate evaluation on the efficacy of communication strategies to promote personal protective behaviors indicated that government-level communications have generally been effective [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although all the models predict that an increased non-infectious air flow rate will reduce infection transmission, there is a lack of high-quality evidence of the effect of enhanced ventilation and air cleaning on transmission [ 20 ].…”
Section: Introductionmentioning
confidence: 99%